Change of Diet, Plasma Lipids, Lipoproteins, and Fatty Acids during Ramadan: A Controversial Association of the Considered Ramadan Model with Atherosclerosis Risk (Journal of Health, Population and Nutrition, 2011)
Different Islamic populations have different alimentary habits, notably during Ramadan. The paper reports the change of diet, lipids, and lipoproteins produced during Ramadan in one Tunisian population. During Ramadan, the study subjects consumed more proteins, cholesterol, vitamin E (p